Drug-Resistant Tuberculosis Presenting as a Testicular Mass: A Case Report - Nuwagira E; Yekosani M; Abraham B; Atwine R; Caleb T; Baluku JB (International Medical Case Reports Journal, 2021)
Edwin Nuwagira,1 Mitala Yekosani,2 Birungi Abraham,2 Raymond Atwine,2 Tuhumwire Caleb,3 Joseph Baruch Baluku4 1Department of Medicine, Mbarara University of Science and Technology, Mbarara, Uganda; 2Department of Pathology, Mbarara University of Science and Technology, Mbarara, Uganda; 3Department of Surgery, Mbarara University of Science and Technology, Mbarara, Uganda; 4Division of Pulmonology, Mulago National Referral Hospital, Kampala, UgandaCorrespondence: Edwin NuwagiraMbarara University of Science and Technology, P.O Box 1410, Mbarara, UgandaTel +256 779096887Email enuwagira@must.ac.ugBackground: Extrapulmonary drug-resistant tuberculosis is extremely rare and is almost always associated with poor treatment outcomes. This is partly due to the difficulty in confirming the diagnosis.Case Presentation: A 40-year-old HIV-negative male presented with a painless scrotal mass, low-grade fever, general malaise, night sweats, and no pulmonary symptoms. He was initially treated for malaria with no improvement. His final diagnosis was rifampicin-resistant tuberculosis following Xpert® MTB/RIF Ultra (Xpert-Ultra) assay performed on a fine needle aspirate of the scrotal mass. Second-line anti-tuberculosis medication was initiated, and the patient is being followed up with directly observed therapy.Conclusion: With the scale-up of Gene-Xpert technology, this case raises awareness about tuberculosis masquerading as a testicular mass and the possibility of extrapulmonary drug-resistant tuberculosis in high endemic areas.Keywords: drug-resistant tuberculosis, genitourinary tuberculosis, extrapulmonary tuberculosis, tuberculous orchitis, sub-Saharan Africa, Uganda